When Is Immigration Selection Discriminatory?. (11th October 2021) - Orgad, Liav
Abstract : Managing global migration is one of the most pressing issues of our time. Traditionally, international law has not generally regulated immigration and citizenship law; it defers to state authority in setting up rules and procedures for entry into the territory and citizenry. The lack of clear regulation—and a commonly accepted methodology on how to evaluate discriminatory borders—creates acute problems in terms of protecting human rights, promoting state interests, and setting up international cooperation. Against this background, this essay offers a legal framework to examine when borders are discriminatory. It includes a three-step process that examines the goals, criteria, and means of immigration and citizenship selection. With almost 300 million international immigrants worldwide living outside their country of origin in 2020, developing such a framework has become an urgent need.